Portable Solid Phase Extraction of Copper, Cadmium and Lead Using Analig ME-02 Chelating Resin and Their Determination by Atomic Absorption Spectrometry - Gaza, Mohamed Abousa; Hakim, Lukman; Sabarudin, Akhmad (The Journal of Pure and Applied Chemistry Research, 2014)
ABSTRACT The adsorption of metallic elements on the solid phase chelating resins is probably the most effective separation and preconcentration methods. In this work, portable Solid phase extraction (SPE) was constructed using a commercially available plastic syringe containing certain amount of the Analiq ME-02 chelating resin. The ability of this portable SPE was evaluated through adsorption-desorption process of copper, lead, and cadmium prior their determination by atomic absorption spectrometry (AAS). Some parameters affecting the adsorption-desorption of these heavy metal ions on the Analiq ME-02, which include effect of pH and concentration of eluent ((HNO3), were investigated in detail. It was found that quantitative adsorptions (> 90%) of copper, lead, and cadmium are obtained at all pHs (4-8) examined, whereas 1 M HNO3 was found to be effective for the desorption of these metals with the recoveries in the range of 93 -114%. Such results indicated that Analig ME-02 has excellent chelating ability (pH-independent) for the adsorption of copper, lead, and cadmium, while portable SPE system provides easiness and effectiveness for collection/preconcentation of metallic elements.